ENERGY AND STRUCTURE STATES OF LOW-LYING BANDS IN 156Gd - Usmanov, P.N.; Yusupov, E.K. (IIUM Engineering Journal, 2020)
The experimental results of the literary and electronic nuclear database for 156Gd were summarized and analyzed. Inertial parameters of rotating core were determined using the Harris method. The theoretical values of energy and wave functions were calculated within the framework of a phenomenological model that takes into account Coriolis mixing of state rotational bands. The calculated energy values were compared with existing experimental data, which were in good agreement. ABSTRAK: Hasil dapatan kajian melalui eksperimen pangkalan data nuklear dan elektronik bagi 156Gd diringkaskan dan dianalisis. Parameter inersia putaran berputar ditentukan menggunakan kaedah Harris. Nilai teori fungsi tenaga dan gelombang dikira dalam kerangka model fenomenologi yang mengambil kira campuran Coriolis pada band putaran keadaan. Nilai pengiraan tenaga dibandingkan dengan data eksperimen memberikan persetujuan yang baik.